INFLUENCE OF EMOTIONAL INTELLIGENCE ON WORK LIFE ALIGNMENT AMONG EMPLOYEES OF MANUFACTURING COMPANIES - SHAMEEM , Dr.A. (International Journal of Psychosocial Rehabilitation, 2020)
Today a lot of emphasis is being placed by organisations in understanding the true influence of emotional intelligence on employees which in turn could also affect the organisation at large. By understanding in detail the effect of emotional intelligence organisations would be better placed in attempting toimprove the an individual’s and overall performance of the organisation. This could have a significant impact on employee’s well- being thereby helping them to have a better level of work life alignment. The primary objective of this paper it to examine the influence of emotional intelligence on work life alignment among employees of manufacturing companies in and around Tamilnadu. It also attempts to identify the constructs influencing emotional intelligence influencing work life alignment among such employees. The study has highlighted that theinfluence of emotional intelligence on work life alignment is positive especially with respect to the constructs of emotional intelligence such as self-awareness and social intelligence.